Use of a Silicone Mask Improves the Reproducibility of Tooth Color Assessment for Whitening Clinical Trials - Pier Francesco Porciani; Simone Grandini; Caterina Perra; Luca Porcu; Valter Torri; Luisa Diomede; Andrea Sarrica (International Journal of Dentistry)
Conclusion: This study indicates that the silicone mask improves the precision of Vita Easyshade, and Rayplicker can be a valid alternative for studies measuring the changes in tooth color after whitening treatments.